Preliminary Safety Assessment of New Azinesulfonamide Analogs of Aripiprazole using Prokaryotic Models - Beata Powroźnik; Karolina Słoczyńska; Krzysztof Marciniec; Paweł Zajdel; Elżbieta Pękala (Tabriz University of Medical Sciences, 2016)
Purpose: Determination of the mutagenic potential of new biologically active compounds is of great concern for preliminary toxicity testing and drug development. Methods: The mutagenic and antimutagenic effects of some quinoline- and isoquinoline-sulfonamide analogs of aripiprazole (1-8), which display potent antidepressant, anxiolytic, and antipsychotic properties, were evaluated using the Vibrio harveyi assay and OSIRIS Property Explorer software. Additionally, the Ames test was used as the reference. Results: In silico prediction showed that compounds 5 (N-(3-(4-(2,3-dichlorophenyl)piperazin-1-yl)propyl)quinoline-7-sulfonamide) and 6 (N-(4-(4-(2,3-Dichlorophenyl)piperazin-1-yl)butyl)quinoline-7-sulfonamide) trigger a mutagenic structural alert. However, this was not confirmed by in vitro assays, as none of the tested compounds displayed mutagenic activity against all tested strains of bacteria. Moreover, compounds 1-8 displayed a protective effect against the mutagenicity induced by a direct acting mutagen NQNO. The most beneficial antimutagenic properties showed compound 5 which exhibited strong antimutagenic properties in all tested V. harveyi strains. High antimutagenic potency of this compound was confirmed in the Ames TA100 assay system. Conclusion: Newly synthesized azinesulfonamide analogs of aripiprazole may be considered as genotoxically safe as they do not display mutagenic activity on the tester strains. Moreover, the tested compounds demonstrated significant antimutagenic properties that can be valuable for prevention of the NQNO genotoxicity. Additionally, it appears that the Vibrio harveyi assay can be applied for primary mutagenicity and antimutagenicity assessment of chemical substances, thus, representing a useful alternative tool for compounds safety evaluation.